Elucidating taxonomic problems of two closely related freshwater prawn lineages of the genus Macrobrachium (Caridea: Palaemonidae): A geometric morphometrics approach - Nogueira, Caio S. [UNESP]; Camargo, Nícholas F.; Pantaleão, João A.F.; Costa, Rogerio C. [UNESP] (Elsevier, 2023)
Macrobrachium amazonicum and Macrobrachium pantanalense are two closely related freshwater prawn species, the latter having been described from populations that were previously considered M. amazonicum. Distinguishing these two lineages from the available taxonomic description can be a complex task due to the morphological similarity of these organisms. In these cases, the investigation of morphological characters that help in the differentiation of these groups is of great value. Thus, the present study aimed to analyze taxonomically informative structures through geometric morphometrics analyses, evaluating the informative potential of these structures in the separation of these lineages. The selected structures were carapace, dactyl, propodus, scaphocerite and telson. The analyzed dactyl and propodus are from the second pair of pereopods (chelipeds). Three populations of each species were analyzed. All structures were photographed and marked with landmarks and semilandmarks for the acquisition of shape variables. The shape and size of all structures differed statistically between the two species, regardless of sex. Among the observed morphometric variations, the most evident were in the carapace and telson. In the carapace, the position of the first ventral tooth of the rostrum is different, while the posterior region of the telson is proportionally thinner in M. amazonicum and wider in M. pantanalense. Our results indicate that the carapace and the telson are informative structures that can help distinguish these two groups. Furthermore, our results support the proposal presented in other studies that M. amazonicum and M. pantanalense may be in a relatively recent process of speciation.
Keywords: Integrative taxonomy; Macrobrachium amazonicum; Macrobrachium pantanalense; Morphometry; Speciation